STRATEGI PEMASARAN PADA PENERBIT MAIZA PUBLISHING DI KABUPATEN ACEH BESAR - Wahyudi Elsyanuri, Faridah Yahya, Irma Anggraini (Universitas Syiah Kuala, 2019)
ABSTRACTPublishers Maiza Publishingis a self publishingbook pioneering effort in Aceh. Publishers are still relatively small and yethave a good distribution network like other publishers therein Indonesia. Even so, the publisher is capable to distribute the book to several region, especially in Aceh.The purpose of this study was to determine (1) how the marketing strategy applied to Maiza Publishing (2) what are the constraints faced by publishers Maiza Publishing. The approachused in this study is a qualitative approach in the form field research that includes observation, interviews, and documentation. There are three stages of data analysis technique: (1) data reduction phase, (2) the stage of presentation of the data, (3) the stage of conclusion and verification. The subjects were the head / ownerof publisher Maiza Publishing, parts distribution, production and marketing. The object of research is to determine the marketing strategy Maiza publisher Publishing that includes STP strategies (Segmentation, Targeting and Positioning) and 4P mix marketing (product, price, place and promotion) and constraints faced. Based on the results of research in the field, researchers discover that the Maiza Publishing has a product that is in demand by consumers certain circles.The marketing strategy that has been done by the publisher Maiza Publishing is promoting effective by way of direct sale to the school with teachers encounter fields and bookstores.Excess publisher Maiza is a clear segmentation and targeting, materials and physical presentation, a good relationship with the bookstore or school and teachers some also are old friends at the alma mater with the author, affordable price of paper, paper quality and appearance of the product.There are several constraints faced by publishers Publishing Maiza were related to the lack of fund, lack of product diversity, physical perishable products, counterfeit products, shipping costs, and payment processing. The conclusion of this study is even with some limitation, publisher Maiza Publishing able to do distribution to the right consumers because they has the right market segmen and target so that the products sell out quickly.Keywords: marketing strategy, publisher